Revegetating Bagacay Mining Site: A review of potential tropical species for phytoremediation of non-essential heavy metals - John Rhey Ymas Dayang (Journal of Degraded and Mining Lands Management, 2017)
Post-mining activities in Samar left serious environmental issues. Albeit it is used to provide prosperity to its constituents, mining in the area brought with it negative impacts. Bagacay Mine, an abandoned mining area in the province was left with enourmous amount of heavy metals. This include As (6-693 ppm), Cu (9-5,279), Pb (22-354 ppm), Hg (1-5 ppm), Zn (<1-7,138 ppm) and Fe (5,900-373,500 ppm). The area was then reforested with Swietenia macrophylla, Leucaena leucocephala, Acacia mangium, Bambusa blumeana and Thysanolaena maxima but only 1 percent survived. This paper touches the nature and effects of the non-essential heavy metals and metalloids present in the area as well as the mechanism of phytoextraction. Additionally, tropical metallophytes which can be used for phytoremediation activities in the future were introduced and reviewed.